Influence of within-and between-row mulching on soil temperature, soil moisture, root development and yield of maize (Zea mays L.) in a tropical soil - Lal, R. (1978)
The effects of zonal mulching on soil physical characteristics and maize (Zea mays) production were investigated for six consecutive maize crops on a tropical Alfisol near Ibadan, Nigeria. Treatments consisted of complete mulch, inter-row mulch, row mulch, and a control. There were differences in soil temperature with respect to mulching, time of the day, and distance from the row. Differences in the maximum soil temperature between mulched and unmulched soil were 3–4°C at 5 cm depth. Soil temperature in the row zone was 2–7°C lower than in the inter-row zone at 15.00 h. Since mulched strips had high earthworm activity, bulk density and penetrometric resistance were low compared with unmulched zones. The mean bulk density of treatments with mulched inter-row was 1.42 and 1.44 gcm−3 compared with 1.50 and 1.64 gcm−3 for treatments with unmulched inter-row, for the 0–10 cm and 10–20 cm depth, respectively. The soil moisture reserve was generally proportional to the area of soil surface covered by mulch. The mean volumetric moisture content in the surface 10 cm of soil was approximately 1.70, 1.58, 1.45, and 1.39 cm for complete mulch, inter-row mulch, row mulch and unmulched control, respectively. The mean and the maximum depth of root penetration were generally greater for treatment with mulched inter-row. In the completely mulched and inter-row mulch treatments, there was a concentration of roots in the surface layer immediately beneath the residue mulch. The inter-row mulch and the completely mulched treatments yielded more than other treatments. Complete mulch yielded 38, 10, and 22% more than the unmulched control in 1973, 1974 and 1975, respectively.